Pendampingan Peningkatan Nilai Tambah Usaha Rumput Laut Masyarakat Pesisir Dusun Badaq Kecamatan Labuhan Haji Kabupaten Lombok Timur - Wira Hendri; Syafira Mahfuzi Ardiyati; Rina Komala; Stevany Hanalyna Dethan; Sahdan Saputra; Ahmad Murad (Insan Kreasi Media, 2023)
Seaweed is one of the sources of livelihood for fishermen besides catching fish. seaweed has a high economic value for the welfare of the people of Badaq Hamlet, Kertasari Village, East Lombok. In its development, seaweed farmers have experienced a decline in production in the last few years due to various factors including a shift in people's understanding of seaweed, fluctuating prices, and traditional planting methods. The community assistance program carried out by the community service team in collaboration with the local community through the theme of increasing the added value of seaweed businesses in coastal communities tries to solve the problem. The results of the mentoring program showed changes in the way coastal communities grow seaweed efficiently and more modern, the community recognizes and understands the types of seaweed that are suitable for cultivation in their place.